1985
DOI: 10.1002/jor.1100030404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tibiofibular motion under load conditions by computed tomography

Abstract: Evaluation of tibiofibular motion in vivo has been possible only by invasive methods. A new noninvasive method has been developed that uses computed tomography (CT). A special device was constructed for use on the CT table to study fibular motion with load placed across the ankle. From dorsal to plantar flexion the fibula moved 1.1 +/- 0.4 mm medially with an accompanying nonsignificant ventral shift and medial rotation. Application of load across the ankle did not significantly alter these findings. In a subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…2b 2c 2d ability. 8,9 This is consistent with the results in our patients, who show no functional loss from fusion of the distal tibia and fibula.…”
Section: Discussionsupporting
confidence: 95%
“…2b 2c 2d ability. 8,9 This is consistent with the results in our patients, who show no functional loss from fusion of the distal tibia and fibula.…”
Section: Discussionsupporting
confidence: 95%
“…Many studies have been performed to investigate the movement of the fibula as a consequence of ankle motion. 1-3,6-9,10,11,13,17-21 The relationship between the tibia and fibula during various movements of the ankle has always been studied as translation and rotation of the fibula with respect to the tibia. While some authors have demonstrated an anterior- posterior translation of the fibula during plantar/dorsiflexion of the ankle, others have not been able to observe it in a significant way.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have reported more than 2 mm of ankle mortise widening, while others have not been able to demonstrate any lateral displacement. 1,2,7,10,18 In this study, lateral displacement of the proximal fibula was in the range of −0.3 to 3 mm for 30 degrees dorsiflexion and in the range of 0.6 to −2 mm for 30 degrees plantarflexion, while the distal fibula had a lateral displacement in the range 2.2 to −0.6 mm for 30 degrees dorsiflexion and 1.2 to −2.5 mm for 30 degrees plantarflexion (negative values indicate medial translation). These values reveal that the amount of lateral displacement of the fibula varied considerably among the specimens tested.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7,13 The syndesmotic ligaments are elastic and are an important component of stress transference; the interosseus membrane normally transmits 30 -50% of body weight to the fibula. 8,11 The tridimensional motion of the fibula is also well established, 4 with the fibula moving distally during the initiation of stance phase and push-off. This motion deepens the mortise and also pulls the fibula medially to further stabilize the talus.…”
Section: Introductionmentioning
confidence: 99%